Community Engagement: Maintaining Satisfaction and Quality to Foster Sustainable Student Loyalty at Bali Hati International School: English - A.A. Sri Arika Deviana Putri; komang widhya sedana putra p (LPPM Universitas Muhammadiyah Tasikmalaya, 2024)
This community engagement program aims to enhance student loyalty and satisfaction at Bali Hati International School, where many students have been enrolled from kindergarten to high school. The phenomenon observed during the internship suggests that most students continue their education at Bali Hati for an extended period despite the school's restrained marketing efforts. This situation warrants further investigation into the factors contributing to this sustainability. According to theory, factors such as service quality, programs, and facilities likely contribute to student loyalty and satisfaction. It is hoped that this initiative will deepen understanding into the factors that contribute to the sustainable student loyalty at Bali Hati International School as well as to understanding the behaviour of consumers that might lead to the development of strategies that improve customer retention. Moreover, it aims to stimulate effective word-of-mouth marketing through positive experiences shared by alumni, students and parents, ultimately supporting the sustainable relationship between students and the school.